Therapeutic value of the metabolomic active neurotransmitter isorhynchophylline in the treatment of spontaneously hypertensive rats by regulating neurotransmitters - Alharbi Homood (De Gruyter, 2021)
Hypertension is one of the most reported cardiovascular and cerebrovascular diseases with significantly high morbidity and mortality rates. This condition threatens the very existence of human beings. Numerous studies conducted earlier revealed the good therapeutic effect of isorhynchophylline on hypertension since the former regulates the metabolic disorders in neurotransmitters. However, the mechanism behind this action is yet to be deciphered. The current study followed the targeted metabolomics method to investigate the changes in the neurotransmitter level in the hippocampus of spontaneously hypertensive rats (SHRs) after the rats were treated with isorhynchophylline. The authors predicted the metabolic pathways involved in extensively modified neurotransmitters. Further, the expressions of metabolism-key enzymes in mRNA and protein levels were also determined. When treated with isorhynchophylline, it induced notably varying metabolomic profiles of the hippocampus in SHRs. Isorhynchophylline perturbed a total of seven extensively modified neurotransmitters as well as the primarily related pathways such as tyrosine and glutamate metabolism. An increase in the key metabolic enzymes such as DDC, MAO, COMT, TH, and DβH was observed in the SHR group, whereas their levels decreased after treatment with isorhynchophylline. The expression of GAD67 established cross-current validity. So, isorhynchophylline has been proved to have potential therapeutic value to treat hypertension via tyrosine and glutamate metabolism in the hippocampus. Further, the current study also opened new ventures to further investigate the working mechanism of isorhynchophylline in hypertension.